Impact of overseas work on parent-child relationship a pilot study (2007)
This pilot study explored college students' perspectives on the impact of overseas work on parent-child relationship. Employing a questionnaire, the responses of the twenty participants revealed that overseas work influenced parent-child relationship in the areas of role performance, communication, involvement in education, other activities and decisions concerning them, discipline, and conflict. From those who gave an overall assessment, 50 percent of the respondents cited that as an effect of overseas work, their relationships with their parents got better than their relationships before that latter went abroad. 25 percent declared that their relationships with their parent/s remained the same while 10 percent mentioned that their relationships with their fathers got worse. Considering the effects of length of work before returning, frequency of visits and gender of OFW parent and child, the first two variables showed effects on parent-child relationship while the latter did not.
Keywords: Parent and child; Filipino foreign workers